E-098 Bolt-patch: a novel theragnostic approach to complex intracranial hypotension. (22nd July 2018) - Xu, R; Chung, C; Moghekar, A; Cho, S; Rao, A; Luciano, M; Geocadin, R; Deib, G; Hui, F
Abstract : Background: Both high and low pressure Cerebral Spinal Fluid can cause headaches. Leaks in the thecal sac may result in low pressure, and identification and treatment of the leak site may be challenging. After leak repair, rebound hypertension has been described, resulting in headaches that respond to carbonic anhydrase inhibitors. Because the success rate of repair is not reliable, post procedural headaches may be either rebound high pressure or low pressure and may be difficult to distinguish. Continuous monitoring of intracranial pressure during percutaneous management of thecal sac discontinuities may help rapidly ascertain treatment success, as well as distinguish the cause of headache post procedure. Methods: The CSF Disorder database was retrospectively queried to identify patients with presumed cerebral spinal fluid hypotension treated with fibrin and blood injection with concomitant intracranial pressure monitoring. Patients were excluded if no follow up information was available. Demographic, clinical and imaging data were recorded and reviewed. Patterns of intracranial pressure were reviewed immediately post procedure and overnight. Results: Nine patients were identified: Immediately post repair, patients experienced transient increase in intracranial pressure during blood/fibrin epidural patch. Day post procedure, 7/9 patients had recordings available. In 2 patients, their pressures returned to baseline, likely indicating treatment failure prompting immediate re-intervention. In 3 patients, their pressures remained high, and above institutional thresholds, and were deemed treatment successes. In one patient, initial monitoring demonstrated higher pressures than expected, and the cause of headaches was deemed to not be related to intracranial hypotension. Impression: Continuous monitoring with percutaneous dural repair may be a therapeutic-diagnostic option for complex intracranial hypotension. In this limited experience, it may accelerate total time to successful dural repair by rapidly identifying failed treatments and help distinguish mimics from true dural leaks. Disclosures: R. Xu: None. C. Chung: None. A. Moghekar: None. S. Cho: None. A. Rao: None. M. Luciano: None. R. Geocadin: None. G. Deib: None. F. Hui: None.